2022
DOI: 10.2174/1570159x19666210325130624
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-wise Functional Connectivity of the Default Mode Network in Epilepsies: A Systematic Review and Meta-Analysis

Abstract: Background: Default mode network (DMN) is recognized to be involved in generation and propagation of epileptic activities in various epilepsies. Converging evidence has suggested disturbed functional connectivity (FC) in epilepsies, which was inferred to be related to underlying pathological mechanisms. However, abnormal changes of FC in DMN revealed by different studies are controversial, which obscures the role of DMN in distinct epilepsies. Objective: The present work aims to investigate the voxel-wise F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 81 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…In line with a previous study, 34,35 we observed higher connectivity between the DMN and other functional networks and within the DMN in patients than in HCs. The DMN is thought to be associated with the generation of epileptic discharges, 36 and the widespread enhancement of connections in patients may be a byproduct of the rapid transmission of electrical signals through the brain during a discharge. 37,38 When we compared the treated patients with the HC group, we showed higher functional and structural connections between the DMN and FPN in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In line with a previous study, 34,35 we observed higher connectivity between the DMN and other functional networks and within the DMN in patients than in HCs. The DMN is thought to be associated with the generation of epileptic discharges, 36 and the widespread enhancement of connections in patients may be a byproduct of the rapid transmission of electrical signals through the brain during a discharge. 37,38 When we compared the treated patients with the HC group, we showed higher functional and structural connections between the DMN and FPN in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Resting‐state functional magnetic resonance imaging (rs‐fMRI) is the most common method to explore functional connectivity by calculating the Pearson correlation coefficient between time series, which characterizes the synergistic activity in the brain. It has been widely used to explore the influence and mechanism of the epileptic network 9–11 . There are many studies of epilepsy that have found abnormal functional connectivity (FC) in multiple brain regions or networks, such as the basal ganglia, cerebral cortex, and default mode network 7,12–14 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used to explore the influence and mechanism of the epileptic network. [9][10][11] There are many studies of epilepsy that have found abnormal functional connectivity (FC) in multiple brain regions or networks, such as the basal ganglia, cerebral cortex, and default mode network. 7,[12][13][14] In general, all these abovementioned studies assumed that functional connectivity is stationary during the scanning process, but in fact, the brain connectivity is highly dynamic in the resting state.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the network-level weighted correlation probability(NWCP) was proposed to achieve the multimodal fusion of neuroimages on the network level in our previous study(Sisi Jiang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The fusion of multimodal provides an effective instrument to integrate the advantage of different neuroimages(Sisi Jiang et al, 2021;Qin et al, 2021). The fusion on the network-level might be adaptive for the disorders of the brain network(SisiJiang et al, 2021). Our previous study proposed the NWCP focused on the static and dynamic functional connections[18], which would re ect the coupling between structural and functional connectivity.…”
mentioning
confidence: 99%